The Role of Religious Moderation in Strengthening the Link Between Local Wisdom and Sustainable Development Goals - Amin, Abdul; Hudin, Hafid; Hakim, Lukmanul; Fahmi, Moch. Riza; Darmadi, Didi; Sumin, Sumin (Abrahamic Religions: Jurnal Studi Agama-Agama, 2025)
This study aims to explore the role of religious moderation as a moderator in the relationship between local wisdom and the achievement of Sustainable Development Goals (SDGs) in Indonesia. Local wisdom is a foundation of values that support social harmony, environmental sustainability, and economic sustainability, but its implementation often faces challenges in plural societies. Religious moderation, which emphasises tolerance, balance and the rejection of extremism, is considered a solution to maintaining social stability and enhancing the connectivity of local values with sustainable development. While there have been many studies on local wisdom and SDGs, there is a lack of studies linking religious moderation as a moderator variable. Using a quantitative approach, this study measures the effect of local wisdom on the achievement of SDGs and examines the moderating role of religion in strengthening the relationship. PLS-SEM analysis shows interesting results regarding the influence of local wisdom, religious moderation, and the achievement of sustainable development goals. The significant path coefficient indicates a strong relationship between local wisdom with religious moderation as a moderator. This finding supports the hypothesis that the higher the level of local wisdom in a community, the stronger the role of religious moderation in mediating the relationship with other variables. However, the analysis also shows an interesting negative relationship between religious moderation and sustainable development. This indicates that an increase in sustainable development is not always directly proportional to an increase in religious moderation.